2020
DOI: 10.21109/kesmas.v15i1.3306
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Exploration of Experiences and Consequences of Health-related Stigma among Indonesians with HIV, Leprosy, Schizophrenia and Diabetes

Abstract: Health-related stigma causes a negative impact on the lives of affected people and undermines the effectiveness of public health programs. This study aimedto explore experiences and consequences of stigma among people affected by four health conditions relevant in Indonesia– HIV (Human ImmunodeficiencyVirus), leprosy, schizophrenia and diabetes. In this qualitative study 40 people affected by the four health conditions in Jakarta and West Java, Indonesia–,were interviewed between March and June 2018. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 46 publications
0
35
0
4
Order By: Relevance
“…HIV, leprosy, schizophrenia, and diabetes. These four conditions were purposively chosen because of their diverse nature and etiology (infectious vs non-communicable), and causes of stigmatization in the Indonesian society [36][37][38][39]44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV, leprosy, schizophrenia, and diabetes. These four conditions were purposively chosen because of their diverse nature and etiology (infectious vs non-communicable), and causes of stigmatization in the Indonesian society [36][37][38][39]44].…”
Section: Methodsmentioning
confidence: 99%
“…It also has high prevalence of noncommunicable health conditions like diabetes mellitus (6.7% in adults) [33] and schizophrenia (around 1%) [34]. Besides the high burden, these four health conditions are also stigmatized in the Indonesian society because of the prevalent social norms, and associated negative stereotypes and misinformation [35][36][37][38][39].…”
Section: The Context Of Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…People with infectious diseases such as HIV and leprosy; mental health conditions like schizophrenia and bipolar disorder; and other non-communicable diseases such as diabetes and cancers are known to be stigmatised because of their health condition (Earnshaw & Kalichman, 2013;Fujisawa & Hagiwara, 2015;González-Torres et al, 2007;Gredig & Bartelsen-Raemy, 2017;Peters et al, 2013). People living with such stigmatised health conditions often live in the same society, but remain isolated and siloed within their own experiences of stigma, suffering its various social, physical and mental health consequences (Corrigan & Rao, 2012;Earnshaw & Kalichman, 2013;Rai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The existing health-related stigma reduction responses follow a similar scenario of fragmentation across different health conditions (Heijnders & Van Der Meij, 2006;Van Brakel, 2006;Weiss et al, 2006), while largely disregarding those with other health conditions who co-exist in the same society, and also missing out on their unique experiential knowledge on living with a stigmatised health condition. Studies have shown that while the origin of stigma across such diseases may be different depending on the different disease-specific features, the experiences of stigma and its consequences are largely similar across a variety of health conditions (Rai et al, 2020;Rao, 2010;Van Brakel, 2006). In such a case, there may be prospects for effectively responding to health-related stigma in the society by bringing together people living with different stigmatised health conditions and their collective knowledge and experiences.…”
Section: Introductionmentioning
confidence: 99%